Metrópole e região na Amazônia: trajetórias do planejamento e da gestão metropolitana em Belém, Manaus e São Luís - SANTOS, Tiago Veloso dos (Universidade Federal do Pará, 2019)
This proposal aims to analyze the relationship between metropolis and region in the Brazilian Amazon. The classical discussion that states the cities and the region dimensions is recomposed due to the new social-spatial dynamics of the metropolization of space, demanding a new look on the relationship established between them. Such a process, however, is not characterized by revealing a possible particularity at the macro-regional level. The configuration of an economical borderline that expands in an unbalanced and differentiated spread in the Amazon inland is also responsible for the formation of distinct sub-regions. The metropolis that have appeared there are product, condition and way to this movement of differentiation, what may be exemplified by the agglomerations of Belém, Manaus and São Luís. Considering, amongst other elements, the relationship that they establish with the region, the urban structure and their type of institutionalization, it is aimed to show the importance and meaning of such metropolitan formations in face of differentiated processes of production of the space in the region. And, although they are product, condition and way of production and reproduction of relations inside a specific regional context in the Amazon, there are not, at the standards of the institutional orders to the metropolis, policies of planning and management that may configure institutional arrangements, so that those particularities may become an articulation component of the urban development in those metropolitan centers. This statement may be verified through the analysis of the characteristics of the policies of planning and management of those spaces, what, most of the times, reproduces the metropolitan institutional arrangements performed in other regions of the country, being the institutionalization of metropolitan regions the most prominent example of this, in a very similar way to the other agglomerations that present more distance than proximity as for the Amazon particularities. Such a characteristic results in the establishment of instruments to the planning and management with questionable degrees and levels of efficiency and efficacy, focusing its standards of implementation.